Partisipasi Simbolik? Keterlibatan Masyarakat dalam Program Rumah Desa Sehat Untuk Pencegahan Stunting di Desa Bangah Sidoarjo - Dina Faradilah; Fierda Nurany; Diana Rahmawati; Lunariana Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2026)
This study aims to analyze the level and depth of community participation in the Healthy Village House Program (RDS) as an effort to prevent stunting in Bangah Village, Sidoarjo Regency. The focus of the research is directed at community involvement in the stages of planning, implementation, utilization of results, and program evaluation. This study uses a qualitative approach with a descriptive method through interview, observation, and documentation techniques. Data analysis was carried out interactively to identify the form, quality, and influence of community participation on the running of the program. The results of the study show that the community has been involved in all stages of the program and has felt real benefits, especially in improving nutritional knowledge, access to health services, and receiving Supplementary Feeding (PMT). However, community participation is still more dominant in the aspect of presence and utilization of program benefits than in strategic decision-making and policy management. Thus, participation in the RDS Program in Bangah Village is on the spectrum between symbolic and substantive, tending to be procedural and semi-substantive. This study confirms that the success of stunting prevention is not only determined by the achievement of the program, but also by the quality and depth of community involvement in village health governance